Analisis Business Model Canvas pada Komodifikasi Konten Wawancara Komeng di Rosi TV - Amalia, Winda; Muqsith, Munadhil Abdul (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Media convergence was born due to changes in times that require audiences to use the internet. Through media convergence, Kompas Gramedia has media that can be consumed online. Media convergence creates content that has been broadcast, then republished by other media, resulting in financial profits. There was content commodification on the Rosi TV program, which broadcast Komeng's interview regarding his success in winning the most votes as a legislative candidate for the 2024 West Java electoral district, which was then republished by other media under the auspices of Kompas Gramedia. Through Convergence Theory, this research aims to find out how content commodification takes place in the context of business development in companies. Using qualitative methods based on literature studies which describe findings descriptively, this research uses BMC Analysis, which compiles nine blocks to determine business strategy by Kompas Gramedia. The economic impact of media convergence was found, resulting in increased income, efficient spending, increased cooperation, and increased content innovation from the Komeng interview on Rosi TV.